2021
DOI: 10.1039/d0ce01718c
|View full text |Cite
|
Sign up to set email alerts
|

The impact of solid solution composition on kinetics and mechanism of [2 + 2] photodimerization of cinnamic acid derivatives

Abstract: The effect of the solid solution composition on the kinetics of solid-state [2 + 2] photocycloadditions was evaluated via a combination of single crystal XRD, FTIR, Raman spectroscopy, and principal component analysis (PCA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Notably, one cannot help noticing that the value of the constant is very close to what found from the ATR-FTIR kinetic analysis by PCA on the single crystal of the same compound. [22] This validates the assumption that the chemical reaction, monitored by the evolution of the intramolecular IR spectrum, and the lattice transformation, followed via the evolution of the intermolecular Raman spectrum, do occur simultaneously. It also represents a striking difference compared to crystal-to-crystal heterogenous reactions, for which Raman measurements spanning both spectral ranges [13,16] have clearly demonstrated that the phase reconstruction takes place with a measurable time delay with respect to the chemical event.…”
Section: Chemphyschemsupporting
confidence: 79%
See 4 more Smart Citations
“…Notably, one cannot help noticing that the value of the constant is very close to what found from the ATR-FTIR kinetic analysis by PCA on the single crystal of the same compound. [22] This validates the assumption that the chemical reaction, monitored by the evolution of the intramolecular IR spectrum, and the lattice transformation, followed via the evolution of the intermolecular Raman spectrum, do occur simultaneously. It also represents a striking difference compared to crystal-to-crystal heterogenous reactions, for which Raman measurements spanning both spectral ranges [13,16] have clearly demonstrated that the phase reconstruction takes place with a measurable time delay with respect to the chemical event.…”
Section: Chemphyschemsupporting
confidence: 79%
“…In Figure S2 the corresponding lattice phonon Raman spectrum for the photodimerization reaction of the system [1H]Cl is also reported. Even though the transformation of [1H]Cl to its dimer takes place on longer time scales, [22] the spectral trend displayed is the same as for [1H]Br.…”
Section: Chemphyschemmentioning
confidence: 74%
See 3 more Smart Citations